Standar Isi, Bahasa, dan Penyajian Buku Tematik Terbitan Mediatama Tema 9 Kayanya Negeriku Seri HOTS - Qotrunnada Salikin; Sudirman; Muhammad Tahir (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
The availability of teaching materials is still minimal and has not facilitated and trained students to learn independently. This study aims to determine the suitability of the content, language, and presentation of the thematic book published by Mediatama Theme 9 Kayanya Negeriku Series HOTS Class IV Curriculum 2013 with the standards set by BSNP. The approach used in this research is a descriptive qualitative approach with the type of content analysis research. The data collection method used is a documentary study method, while the data analysis in this study uses data analysis according to Krippendorff. The results of the analysis show that according to the standard, the percentage obtained is 100% (very suitable), the language standard is 97.2% (very suitable), and the standard is 91.7% (very suitable).